THE TIME MACHINE - Wells, H. G. (Herbert George), 1866-1946.; Cameron, Lou, 1924-1910; Graham, Lorenz (Newbury, Berkshire : CCS Books, 2019)
Wells's classic tale tells the story of the unnamed time traveller, who travels thousands of years into the future, where he encounters the strange, child-like people, the Eloi, and the terrifying underground race, the Morlocks. Classics Illustrated tells this wonderful tale in colourful comic strip form, offering an excellent introduction for younger readers. This edition also includes a biography of H. G. Wells, theme discussions and study questions, which can be used both in the classroom or at home to further engage the reader in the story.
Primary.
Keywords: Time travel -- Comic books, strips, etc; Science fiction comic books, strips, etc; Science fiction comics; Graphic novels; Comics adaptations